Modyfikacje klasycznego pojęcia prawdy - Czarnocka, Małgorzata (Filozofia Nauki, 1996)
In the article different modification of classical concept of truth are considered. The author claims that analyses of cognitive processes and ways of acquiring knowledge should be taken into account in such modification.